Cytosolic flagellin-induced lysosomal pathway regulates inflammasome-dependent and -independent macrophage responses - Lage, Silvia Lucena [UNIFESP] (2013)
NAIP5/NLRC4 (neuronal apoptosis inhibitory protein 5/nucleotide oligomerization domain-like receptor family, caspase activation recruitment domain domain-containing 4) inflammasome activation by cytosolic flagellin results in caspase-1-mediated processing and secretion of IL-1 beta/IL-18 and pyroptosis, an inflammatory cell death pathway. Here, we found that although NLRC4, ASC, and caspase-1 are required for IL-1 beta secretion in response to cytosolic flagellin, cell death, nevertheless, occurs in the absence of these molecules. Cytosolic flagellin-induced inflammasome-independent cell death is accompanied by IL-1 alpha secretion and is temporally correlated with the restriction of Salmonella Typhimurium infection. Despite displaying some apoptotic features, this peculiar form of cell death do not require caspase activation but is regulated by a lysosomal pathway, in which cathepsin B and cathepsin D play redundant roles. Moreover, cathepsin B contributes to NAIP5/NLRC4 inflammasome-induced pyroptosis and IL-1 alpha and IL-1 beta production in response to cytosolic flagellin. Together, our data describe a pathway induced by cytosolic flagellin that induces a peculiar form of cell death and regulates inflammasome-mediated effector mechanisms of macrophages.